Case Report: Remarkable breakthrough: successful treatment of a rare intracranial mesenchymal, FET::CREB fusion-positive tumor treated with patient-tailored multimodal therapy - D’Antonio, Federica; Rossi, Sabrina; Giovannoni, Isabella; Alaggio, Rita; Carai, Andrea; Milano, Giuseppe M.; Cacchione, Antonella; Cancellieri, Alessandra; Gessi, Marco; Antonelli, Manila; Colafati, Giovanna S.; Megaro, Giacomina; et al. (Frontiers in Oncology, 2023)
Background Intracranial mesenchymal tumors are a rare type of neoplasm (0.3% of all soft tissue tumors) characterized by a fusion of a FET family gene (usually EWSR1, rarely FUS) to CREB family genes (CREB1, ATF1, and CREM) with a slow-growing and favorable prognosis. Mesenchymal tumors are most frequently localized in the subcutaneous tissue (typically in the limbs and hands) of young adults and have rarely been diagnosed in the central nervous system. Surgery is the gold standard treatment; adjuvant radiation therapy and chemotherapy with sarcoma-based regimens have been used in rare cases when complete surgical excision was not recommended. In terms of prognosis, these tumors show a tendency for local relapse. The longest patient outcomes reported in the literature are five years. Case description This case describes a 27-year-old woman with unconventional extracranial metastatic sites of myxoid intracranial mesenchymal tumor FET::CREB fusion-positive and high expression of PD-1 (40%) and PD-L1 (30%). Based on clinical, molecular, and histological characteristics, she underwent various local and systemic therapies, including surgery, proton beam therapy, the use of immune checkpoint inhibitors, and chemotherapy. These treatments led to a complete remission of the disease after eight years from tumor diagnosis. Conclusions Our case sheds light on the importance of precision medicine and tailored therapy to explore new treatment opportunities for rare or unknown tumor entities.